Monetary and non-monetary determinants of inflation volatility - Bokava, Sviatlana Y.; Abakumova, Juliet G. (Journal of the Belarusian State University. Economics, 2018)
The dynamics of inflation of the Republic of Belarus for 2003–2017 years, on the basis of statistical analysis has been constructed an econometric model of inflation on monthly data from January 2012 to December 2016. To account for the conditional heteroscedasticity and autocorrelation of the generalized model used autoregressive conditional heteroskedasticity (GARCH-model) for the study of inflation based on the statistics of the National Bank of Republic of Belarus.
Keywords: ARCH-model; GARCH-model; indicator of inflation; basic rate of inflation; augmented Dickey – Fuller test